If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 = -7 Reorder the terms: 1 + 2x = -7 Solving 1 + 2x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = -7 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = -7 + -1 2x = -7 + -1 Combine like terms: -7 + -1 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 2y-(y+2)=3y | | x^3+3x^2-2x-6=0 | | 2x^4+26x^2+72=0 | | x=15+75 | | 2a^2-25b^2+10a+25-10ab=0 | | x^3+6x=6 | | 3f+9=12 | | -6v=-48 | | -2c=10 | | 3x^4+15x^2-72=0 | | 12x+10=2x+5 | | 4v=-20 | | 6z=-60 | | -9z=-9 | | 4x^2-24x+9=49 | | -9=-20 | | 7b=-28 | | 4z+6+3=17 | | 7a=-14 | | -9a=18 | | 20x=3x+17 | | 4v=32 | | 8z=-24 | | 4x^2-24x-40=0 | | 2x+10=x+74 | | 12x-7=-12x+17 | | 4+t=13 | | 8x-3=2x-45 | | 81-16x^4=0 | | -8x+4=36 | | x-15=4x-3 | | a+2b=2b |